Effect of financial deepening on economic growth: Does it encourage income group transition? - Yuliia Shapoval (LLC "CPC "Business Perspectives", 2021)
The rapid growth of financial deepening raises the problem of its effect, beneficial for economic development. This paper aims to demonstrate the relationship between economic growth (GDP per capita growth, GNI per capita) and financial depth (domestic credit to private sector and credit availability) in 142 countries, split into four income groups, over 2000–2020, using correlation analysis and data from the World Bank and the IMF. Besides, a comparative analysis of domestic credit to the private sector, economic freedom, Gini index, total government expenditure and national savings of countries that increased their income group status over 2011–2020 is presented. Financial deepening (increased credit availability and expansion of domestic credit to the private sector) encourages economic growth (via GNI per capita and GDP per capita growth). Although the presence of a nonlinear relationship between economic growth (GDP per capita growth) and financial depth (domestic credit to private sector and credit availability) over 1991–2020 is insufficient, there is a linear relationship between GNI per capita and credit availability, between credit availability and domestic credit to the private sector for the same sample of countries over 2000–2020. Meanwhile, there is a tendency towards a decrease in the correlation between GNI per capita and GDP per capita growth. Given the revealed linear correlation between domestic credit to the private sector and GNI per capita, financial deepening positively impacts income growth, and this dependence strengthens with increasing income levels. Target values of domestic credit to the private sector are proposed for the income group transition. AcknowledgmentThe paper was funded as a part of the “Relationship between financial depth and economic growth in Ukraine” research project (No. 0121U110766), conducted at the State Institution “Institute for Economics and Forecasting of the NAS of Ukraine”.